2021
DOI: 10.1159/000518011
|View full text |Cite
|
Sign up to set email alerts
|

Fluocinolone Implant for Idiopathic Retinal Vasculitis, Aneurysms, and Neuroretinitis Syndrome: A Case Report

Abstract: Idiopathic retinal vasculitis, aneurysms, and neuroretinitis (IRVAN) syndrome is a rare and progressive disorder that predominantly affects both the eyes of young female individuals and can threaten visual function. Peripheral ischemia and macular exudation are common findings in patients. The treatment options include panretinal photocoagulation (PRP), systemic immunosuppression, and intravitreal antiangiogenic and corticosteroid therapy. Fluocinolone acetonide intravitreal implant is approved for the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The epidemiology of the syndrome assured that the majority of patients were young females [ 1 , 5 ]. Our literature review included publications about cases of 10 females and 6 males, and the average age at the time of diagnosis was 28.8 years (range, 9–60 years) [ [2] , [3] , [4] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ]. Whereas, Samuel et al study determined the average age of diagnosis at 31.5 years (range, 9–60 years) in their study which involved 22 patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The epidemiology of the syndrome assured that the majority of patients were young females [ 1 , 5 ]. Our literature review included publications about cases of 10 females and 6 males, and the average age at the time of diagnosis was 28.8 years (range, 9–60 years) [ [2] , [3] , [4] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ]. Whereas, Samuel et al study determined the average age of diagnosis at 31.5 years (range, 9–60 years) in their study which involved 22 patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study, there was no association between IRVAN and any systemic disorder [ 6 ]. The majority of reviewed cases had a clear medical history and negative serum tests [ [2] , [3] , [4] , [10] , [11] , [12] , [13] , [14] , [15] , 17 ], in comparison to positive human leukocyte antigen B51 (HLA-B51) and antinuclear antibodies (ANA) at 1/50 titer in one case [ 9 ]. AM Abu El-Asrar et al reported a case of association between Allergic fungal sinusitis (AFS) and IRVAN syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations